2012
DOI: 10.5430/jst.v2n5p5
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative intraperitoneal chemotherapy for advanced gastric cancer

Abstract: <span style="font-family: Times New Roman; font-size: small;"> </span><p class="a"><strong><span>Background-Aims:</span></strong><span> Perioperative intraperitoneal chemotherapy either under normothermia during the early postoperative period (EPIC) or intraoperatively combined with heat (HIPEC) has been shown to improve survival after radical resection of advanced gastric cancer. The purpose of the study is to compare the effect of EPIC and HIPEC in patients und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…19 The average costs of CRS þ HIPEC per patient varies from about 20,000-80,000 USD. [20][21][22][23][24][25][26] Because of these reasons, this research is important to address the significant uncertainty about the benefits of an intervention that carries potential risk of harm to patients and major costs to the NHS.…”
Section: Why Is This Research Important To Patients and Health And Ca...mentioning
confidence: 99%
See 1 more Smart Citation
“…19 The average costs of CRS þ HIPEC per patient varies from about 20,000-80,000 USD. [20][21][22][23][24][25][26] Because of these reasons, this research is important to address the significant uncertainty about the benefits of an intervention that carries potential risk of harm to patients and major costs to the NHS.…”
Section: Why Is This Research Important To Patients and Health And Ca...mentioning
confidence: 99%
“…Whilst some reports have shown a 30‐day mortality after CRS + HIPEC of 1%–3%, 2 and a major complication rate of 32%, 2,18 data from high volume centers has shown that major complication rates are around 10%–15% and a 90‐day mortality of 1% 19 . The average costs of CRS + HIPEC per patient varies from about 20,000–80,000 USD 20–26 . Because of these reasons, this research is important to address the significant uncertainty about the benefits of an intervention that carries potential risk of harm to patients and major costs to the NHS.…”
Section: Background and Rationalementioning
confidence: 99%